Análisis de un sistema automatizado de gestión y administración de recursos en la Empresa Piladora Aracely. - Pérez Melendres, Manuel Antonio (2022)
Summary In the present case study, an analysis of an automated resource system will be carried out, as the administrative and operational resources of Piladora Aracely are managed, in order to detect the causes of loss of documents and performance of the company, the line of investigation of information systems and a descriptive and qualitative method, which allowed to measure several main aspects which provided data and important information to study them and reach the pertinent conclusions and provide recommendations to the loss of information. In the technical feasibility it was possible to obtain that the resources obtained by the Piladora are adequate in addition to having the detailed specifications of (hardware and software), which will be able to support the execution of the process that implies the use of the system in the computer, therefore Therefore, it would lead to a better operation with this new acquisition. It has been possible to determine through case study. analysis that the implementation of an automated resource management and administration system in the company PILADORA 'ARACELY' provides a solution to the identified problem, that is, if it is of utmost importance the implementation of the same.